1990
DOI: 10.1159/000120535
|View full text |Cite
|
Sign up to set email alerts
|

Diastematomyelia in 172 Children: The Impact of Modern Neuroradiology

Abstract: The increasing sophistication of neuroradiology has significantly and progressively improved the diagnosis of diastematomyelia in 172 children presenting at the Hospital for Sick Children, Toronto, over a 40-year period. Standard radiography, computed tomography and magnetic resonance imaging are all necessary to accurately assess all the facets of this most interesting of spinal cord anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
5

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 1 publication
0
40
0
5
Order By: Relevance
“…Among these, the present case is the only one with a dorsally attached bony spur. Extensive search in the English literature has not revealed a similar case [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19]. Even the recently published series on SCM does not mention such an entity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the present case is the only one with a dorsally attached bony spur. Extensive search in the English literature has not revealed a similar case [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19]. Even the recently published series on SCM does not mention such an entity [14].…”
Section: Discussionmentioning
confidence: 99%
“…Pang [1] reported on 2 cases of composite-type SCM among 39, and Erşahin et al [15] reported on 4 cases of this type among 74. The frequency of composite-type SCM was less than 1% in the series reported by Harwood-Nash and McHugh [16]. Gower et al [17] had only 1 patient with composite-type SCM with a bone spur at the midcleft and another at the caudal end of the cleft.…”
Section: Discussionmentioning
confidence: 99%
“…Esta alteração é caracterizada pela divisão da medula no plano sagital com separação ou não do saco dural e pode estar associada a várias outras anomalias como mielomeningocele, seio dérmico, seringomielia, lipomas e alterações ósseas, incluindo a escoliose. A diastematomielia é 2 a 3 vezes mais comum em pacientes do sexo feminino e é mais frequente na região lombar, mas pode estar localizada em todas as áreas da coluna incluindo a região cervical e a transição crânio-cervical 4,[8][9][10][11] . Em geral, é diagnosticada em crianças e os sintomas mais frequentes são aqueles relacionados às alterações ortopédicas, à bexiga neurogênica e ao déficit motor, que pode se apresentar com caráter progressivo, sugerindo síndrome da medula presa 11 .…”
Section: Discussionunclassified
“…Estas lesões cutâneas geralmente estão situadas na linha média mas não necessariamente correspondem ao nível de lesão da diastematomielia 12 . A radiografia simples de coluna é o exame indicado para a investigação inicial e evidencia imagem compatível com esporão ósseo em 20 a 60% dos casos 10,14 . Outras evidências incluem alterações das lâminas, como fusão vertical, e dos pedículos com separação deles ou diminuição da sua altura; hemivértebras, fusão do corpo vertebral, redução do tamanho das vértebras e duplicação ou ausência de processos espinhosos.…”
Section: Discussionunclassified